Functional redundancy and niche complementarity maintain nitrification stability in rapid sand filters - Palomo, Alejandro; Fowler, S. Jane; Nemer, Ibrahim M.; Valverde-Pérez, Borja; Zheng, Yan; Ma, Yunjie; Smets, Barth F. (Frontiers in Microbiology, 2026)
Nitrification in drinking water biofilters is mediated by a complex guild of ammonia oxidizers, yet the mechanisms facilitating the coexistence of these functionally redundant nitrifier guild members are not well understood. Using lab-scale columns packed with material from a full-scale groundwater-fed rapid sand filter (RSF), we investigated the responses of co-occurring complete ammonia-oxidizing (comammox) Nitrospira, ammonia-oxidizing bacteria (AOB), and archaea (AOA) to operational disturbances over 30 days. Overall, robust nitrification was maintained, with ammonium removal scaling proportionally with substrate loading under oxic conditions. A marked depth-dependent differentiation of nitrifier biomass was identified in the source filter; a 66-fold enrichment of Nitrospira in the top layer determined initial removal capacity, while the bottom layer adapted through both nitrifier proliferation and load-dependent physiological upregulation. Bacterial nitrifiers were primarily structured by strong legacy effects and spatial gradients. AOA abundance, however, was independent of layer origin and governed by environmental conditions, exhibiting a preference for colder (10 °C) and oxygen-limited conditions. Substrate-dependent niche partitioning based on free-ammonia concentration was evident among all nitrifier guild members, enabling stable coexistence without competitive exclusion. Further, temperature-dependent turnover between comammox clades A and B occurred independently of substrate or oxygen conditions, suggesting fine-scale ecological partitioning between phylogenetically distinct comammox species. These findings indicate that functional redundancy, maintained by niche complementarity among diverse members of the nitrifier guild, underpins the stability of RSF nitrification under environmental disturbances. This study provides a mechanistic framework for understanding microbial coexistence in engineered oligotrophic ecosystems facing fluctuating environmental conditions.